2020
DOI: 10.3348/kjr.2019.0232
|View full text |Cite
|
Sign up to set email alerts
|

B-Value Optimization in the Estimation of Intravoxel Incoherent Motion Parameters in Patients with Cervical Cancer

Abstract: Diffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC) are useful for evaluating and characterizing the primary tumor in cervical cancer (1), assessing metastatic lymph node involvement (2), and monitoring treatment response (3-5). However, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…Finally, the choice of b-values was probably not optimal; b-value optimization may improve IVIM estimates. 30,31…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the choice of b-values was probably not optimal; b-value optimization may improve IVIM estimates. 30,31…”
Section: Discussionmentioning
confidence: 99%
“…We hope, therefore, that these methods will be included in future phantom studies. Finally, the choice of b‐values was probably not optimal; b‐value optimization may improve IVIM estimates 30,31 …”
Section: Discussionmentioning
confidence: 99%
“…In our study, a large sample size of 184 patients was analyzed, and thus, the results based on the optimal threshold b values were more persuasive for the detection of the axSpA activity in sacroiliitis. Previous studies confirmed that, with a carefully selected threshold b value, the error could be reduced in the measurement of parameters from IVIM DWI [ 22 , 23 ]. However, it is demonstrated that the optimal threshold b value is dependent on the location of the body, such as 40 s/mm 2 in breast cancer and 100 s/mm 2 in cervical adenocarcinoma [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 82%
“…In our study, there was a significant difference in the D value of the PMI-positive and PMI-negative groups. Perucho et al [ 25 ] showed that high FIGO stages had higher D ∗ values than low stages, but D values had no significance in distinguishing between high and low stages. The D value, excluding the low b value perfusion, represents pure water molecule diffusion of the tumor.…”
Section: Discussionmentioning
confidence: 99%